Menopause and hormone replacement therapy. Issue 4 (April 2015) - Short, Hannah
A woman born in 1970 can expect to spend one-third of her life post-menopause. The climacteric period can be challenging for both patients and health care providers, with menopausal symptoms and the physical effects of oestrogen deficiency accounting for a significant proportion of primary care consultations. The use of hormone replacement therapy (HRT) remains a controversial topic and misleading information is widespread. Good management of post-reproductive health can have a significant impact on a woman's current and future well-being. This article aims to provide an overview of the physical, psychological and social consequences of menopause, the menopause consultation and the role of HRT in its management.